If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + 19 = x + 7 Reorder the terms: 19 + -3x = x + 7 Reorder the terms: 19 + -3x = 7 + x Solving 19 + -3x = 7 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 19 + -3x + -1x = 7 + x + -1x Combine like terms: -3x + -1x = -4x 19 + -4x = 7 + x + -1x Combine like terms: x + -1x = 0 19 + -4x = 7 + 0 19 + -4x = 7 Add '-19' to each side of the equation. 19 + -19 + -4x = 7 + -19 Combine like terms: 19 + -19 = 0 0 + -4x = 7 + -19 -4x = 7 + -19 Combine like terms: 7 + -19 = -12 -4x = -12 Divide each side by '-4'. x = 3 Simplifying x = 3
| 4u-u=12 | | 3a-(a-2)+6=12 | | X+(2x-1)=44 | | 9m-m+3=-2(m-1) | | 21x^3+10x^2+x=0 | | 2(6x+4)+3(3x+5)=-103 | | 8(10a)-6= | | -2.7g-8.4=6.072+0.03g | | y=16x^2+8x+1 | | 3x+6forx=12 | | (65-11y)/3= | | 27=-9b | | 3x=16x-4 | | 5/8x-15 | | y^2+(y-7)(y-7)=25 | | 6x7/11 | | 11x-1=x+99 | | 20x^2-5x/5x | | 18x1/9 | | 18z+3+5z-3=180 | | 5z+2z=6z+5 | | (d-3)(d+5)=12 | | 0.007(1-k)+0.03(k-8)=1 | | (2w+80)+72=180 | | 2x+80=72 | | d-2/5=3/4 | | 8/6x15 | | (2w+80)=72 | | 8x+20=x+15 | | -63x^2-23x+56=0 | | (8x^4y^9)^(1/3) | | 2z+2.5=4z-1.5 |